D-region impact area of energetic electron precipitation during pulsating aurora - E. Bland; F. Tesema; N. Partamies (Annales Geophysicae, 2021)
A total of 10 radars from the Super Dual Auroral Radar Network (SuperDARN) in Antarctica were used to estimate the spatial area over which energetic electron precipitation (EEP) impacts the D-region ionosphere during pulsating aurora (PsA) events. We use an all-sky camera (ASC) located at Syowa Station to confirm the presence of optical PsAs, and then we use the SuperDARN radars to detect high frequency (HF) radio attenuation caused by enhanced ionisation in the D-region ionosphere. The HF radio attenuation was identified visually by examining quick-look plots of the background HF radio noise and backscatter power from each radar. The EEP impact area was determined for 74 PsA events. Approximately one-third of these events have an EEP impact area that covers at least 12 ∘ of magnetic latitude, and three-quarters cover at least 4 ∘ of magnetic latitude. At the equatorward edge of the auroral oval, 44 % of events have a magnetic local time extent of at least 7 h, but this reduces to 17 % at the poleward edge. We use these results to estimate the average size of the EEP impact area during PsAs, which could be used as a model input for determining the impact of PsA-related EEP on the atmospheric chemistry.